Silencing the guns in Africa beyond 2020: Challenges from a governance and political perspective - Victor H Mlambo (Taylor & Francis Group, 2021)
The need to silence the guns, and consolidate peace and stability in Africa is reflected in the African Union’s Agenda 2063, which calls for a peaceful and politically stable Africa. This paper examines the practicality of silencing the guns beyond 2020 and its associated challenges. To accomplish this, the paper employed a review of the relevant literature to examine whether guns can be silenced in Africa going forward. It suggests that silencing the guns beyond 2020 at this point is not possible. The legacies of colonialism, the role of external actors in the affairs of Africa and the increasing number of ethnoreligious conflicts are challenges that need to be addressed before the possibility of silencing the guns can be considered. AU member states need to forge unity on collectively resolving security issues. Failure to do so will see Africa continue to be at the mercy of armed conflicts, political instability and external actors.